Chain extension of poly (ethylene terephthalate) by reactive extrusion with secondary stabilizer - Bimestre,Breno Heins (2012)
Poly(ethylene tereftalate) (PET) is a polymer highly susceptible to the hydrolytic reactions that occur during applications and mainly in thermomechanical processing. These reactions lead to the decrease of molecular weight of the polymer, limiting the recycling number of the material. The reactive extrusion of the PET in presence of chain extenders is an alternative to recover mechanical and rheological properties that were depreciated by the polymer degradation. In this study, PET wastes from nonwoven fabrics production were extruded in presence of the secondary stabilizer Irgafos 126 (IRG) on variable concentrations. The results showed that Irgafos 126 increased molecular weight, decreased crystallinity and changed processing behavior of the PET, similarly to the effects produced by the well-known chain extender pyromellitic dianhydride (PMDA), showing that the secondary stabilizer Irgafos 126 can also act as a chain extender for the PET.